2021
DOI: 10.1055/a-1099-9332
|View full text |Cite
|
Sign up to set email alerts
|

Empfehlungen zur neuropsychologischen Diagnostik beim Morbus Parkinson

Abstract: Zusammenfassung Hintergrund Das Vorliegen von leichten kognitiven Störungen bei der Parkinson-Erkrankung ist aktuell der beste Prädiktor für die Entwicklung einer Demenz bei Morbus Parkinson. Expertengruppen der Movement Disorder Society haben für die Diagnose leichter kognitiver Störungen und Parkinson-Demenz standardisierte diagnostische Verfahren vorgeschlagen. Diese können aufgrund fehlender Übersetzungen oder geeigneter Normen nicht ohne Weiteres auf den deutschsprachigen Raum angewendet werden.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Thus, false-positive diagnoses will be reduced. In order to decrease the risk of false-negative diagnoses, patients who show borderline performance (e.g., a percentile rank of 20) will, however, need to go through additional testing (level II diagnostics) to validate the finding [ 75 , 76 ]. However, this approach is not uncommon in clinical neuropsychology and screening instruments are not used solely during the assessment of cognitive performance anyway.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, false-positive diagnoses will be reduced. In order to decrease the risk of false-negative diagnoses, patients who show borderline performance (e.g., a percentile rank of 20) will, however, need to go through additional testing (level II diagnostics) to validate the finding [ 75 , 76 ]. However, this approach is not uncommon in clinical neuropsychology and screening instruments are not used solely during the assessment of cognitive performance anyway.…”
Section: Discussionmentioning
confidence: 99%
“…The CERAD-PLUS battery has been shown to be accurate and useful in identifying cognitive impairment in PD patients (Karrasch et al, 2013;Camargo et al, 2018), while both the WIE [English version: Wechsler Adult Intelligence Scale (Yamawaki et al, 2020;Chen et al, 2021)] and the Leistungsprüfsystem 50 + batteries have been utilized in PD-cognition studies (Fengler et al, 2016;Kalbe et al, 2016). Furthermore, a recent systematic literature review identified specific tests used in PD research that have been normed for German-speaking populations and their corresponding cognitive domain (Liepelt-Scarfone et al, 2021). The authors presented guidelines for the neuropsychological assessment of PD patients in the German language, with their findings supporting our chosen tests and domains.…”
Section: Patient Measuresmentioning
confidence: 99%